2021
DOI: 10.1186/s41235-021-00290-5
|View full text |Cite
|
Sign up to set email alerts
|

Expert camouflage-breakers can accurately localize search targets

Abstract: Camouflage-breaking is a special case of visual search where an object of interest, or target, can be hard to distinguish from the background even when in plain view. We have previously shown that naive, non-professional subjects can be trained using a deep learning paradigm to accurately perform a camouflage-breaking task in which they report whether or not a given camouflage scene contains a target. But it remains unclear whether such expert subjects can actually detect the target in this task, or just vague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The veto effect is all the more striking in the cases of Experiments 1 and 2, where the subjects were expert camouflage-breakers. We have previously reported that expert camouflage-breakers are so skilled in their task that they can detect the camouflaged target even after brief viewing the stimulus, even as briefly as 50 ms, which does not permit extended scrutiny or eye movements ( Chen and Hegdé, 2012a ; Branch et al, 2021 ). In this specific sense, detecting the target is relatively easy for the expert subjects, so that the subjects could easily cross-check the prior information against the visual evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The veto effect is all the more striking in the cases of Experiments 1 and 2, where the subjects were expert camouflage-breakers. We have previously reported that expert camouflage-breakers are so skilled in their task that they can detect the camouflaged target even after brief viewing the stimulus, even as briefly as 50 ms, which does not permit extended scrutiny or eye movements ( Chen and Hegdé, 2012a ; Branch et al, 2021 ). In this specific sense, detecting the target is relatively easy for the expert subjects, so that the subjects could easily cross-check the prior information against the visual evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The image manipulations used for the ODDS scenes were modeled after those used by Hess et al ( 2016 ), who studied search for camouflaged targets. “Camouflage-breaking” can be considered a special instance of visual search wherein observers must identify objects of interest that blend into the background (Branch et al, 2021 ). The ODDS stimuli might be useful for understanding search behaviors in tasks that routinely require camouflage breaking.…”
Section: Discussionmentioning
confidence: 99%
“…If a target is sufficiently well-camouflaged, it can be all but impossible to find it even if it is in ‘plain sight’ [ 22 , 25 ]. Thus, searching for a camouflaged object is a special case of a visual search [ 25 , 26 ].…”
Section: Experiments 1: Characterization Of the Relationship Between ...mentioning
confidence: 99%
“…By contrast, the task difficulty in conventional visual search stimuli, such as the aforementioned array with O- and Q-shapes, arises from having to distinguish the targets from the distractors and vice versa, and not from the difficulty of segmenting them. This is because both the target and the distractors are typically highly distinguishable from the background and from each other in conventional visual search stimuli [ 26 ].…”
Section: Experiments 1: Characterization Of the Relationship Between ...mentioning
confidence: 99%